2011
DOI: 10.1088/0004-637x/745/1/6
|View full text |Cite
|
Sign up to set email alerts
|

A Global Two-Temperature Corona and Inner Heliosphere Model: A Comprehensive Validation Study

Abstract: The recent solar minimum with very low activity provides us a unique opportunity for validating solar wind models. During CR2077 (2008 November 20 through December 17), the number of sunspots was near the absolute minimum of solar cycle 23. For this solar rotation, we perform a multi-spacecraft validation study for the recently developed three-dimensional, two-temperature, Alfvén-wave-driven global solar wind model (a component within the Space Weather Modeling Framework). By using in situ observations from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 88 publications
2
42
0
Order By: Relevance
“…These observations are even more powerful by combining them with remote observations of coronal plasma, which reveals details about CME expansion and solar wind source regions (e.g., Gruesbeck et al 2011;Jin et al 2012). These data are further complemented by recent simulations (Lynch et al 2011) of ICME and solar wind (Jin et al 2012) charge state composition.…”
Section: Plasma Evolutionmentioning
confidence: 94%
See 1 more Smart Citation
“…These observations are even more powerful by combining them with remote observations of coronal plasma, which reveals details about CME expansion and solar wind source regions (e.g., Gruesbeck et al 2011;Jin et al 2012). These data are further complemented by recent simulations (Lynch et al 2011) of ICME and solar wind (Jin et al 2012) charge state composition.…”
Section: Plasma Evolutionmentioning
confidence: 94%
“…The in situ charge state composition, therefore, complements remote observations and provides a unique and very important measure of the heating and expansion of the solar wind near the Sun (e.g., Fenimore 1980;Galvin 1997;Henke et al 1998;Lepri and Zurbuchen 2004;Reinard 2005;Zurbuchen and Richardson 2006). Used in combination, ion freeze-in states can be used to map out the heating and expansion rates of CMEs and as well as the ambient solar wind (e.g., Buergi and Geiss 1986;Esser and Edgar 2001;Lynch et al 2011;Jin et al 2012) Numerous studies have shown the value of ion charge states as identifiers of ICMEs, finding that MCs are more likely to exhibit a higher composition of elevated charge states than non-MC ICMEs (e.g., Henke et al 1998). Figure 16 (adapted from Zurbuchen and Richardson 2006) provides an example of ICME charge state signatures shown in conjunction with the MHD plasma quantities, supra-thermal electron populations and magnetospheric DST.…”
Section: Plasma Evolutionmentioning
confidence: 97%
“…However, in current-sheetfree locations, the turbulence scaling law of Iroshnikov (1964) and Kraichnan (1965) is obeyed, where turbulent power is proportional to k −3/2 rather than k −5/3 , where k is the Alfvén wave number. The difference in damping rates does not have a significant impact on our model, as the damping length has been chosen to produce model results that closely match the observed density, temperature, and velocity of the solar wind (Jin et al 2012).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Finally, the Wang-Sheeley-Arge empirical model is used to determine the Alfvén wave pressure necessary to produce the observed solar wind speeds. This coronal model has been validated by an extensive comparison with both in situ and remote observations (Jin et al 2012). …”
Section: System Of Equationsmentioning
confidence: 99%
“…Liu et al (2011) used the Space Weather Modeling Framework (SWMF; Tóth et al 2005), a 3D magnetohydrodynamic (MHD) simulation code, to simulate the propagation of CMEs and the associated shocks and found that near the Sun the magnetic field lines drape around the flux rope (the CME ejecta) and align themselves with the magnetic field in the flux rope. More recently, Manchester et al (2012) and Jin et al (2012Jin et al ( , 2013 implemented the two-temperature (2T) model of van der Holst et al (2010) in the MHD BATS-R-US code (Powell et al 1999) within the SWMF. They demonstrated that most of the 2T model outputs can fit WL observations of CMEdriven shocks by LASCO C2 and STEREO very well.…”
Section: Introductionmentioning
confidence: 99%